Methodology of Research Discourse - Alexei Dmitrievich Voskressenski; В. Я. Белокреницкий; С. И. Лунёв; К. А. Ефремова (Сравнительная политика)
The section is devoted to the comparative analysis of Russian and foreign Oriental studies, their similarities and differences, as well as to the analysis of the methodology used by historians and political scientists in the study of modern political process in Asia and Africa. The authors also explain the differences between Western and non-Western societies, as well as the advantages and disadvantages of the analytical and spatial approaches to building typology of Eastern regions.